(untitled) (Research, Society and Development, 2023)
The physiological process of swallowing plays a vital role in transporting saliva, food, and fluids from the mouth to the stomach through a complex reflex, involving components of the stomatognathic system that collaborate with the central nervous system through neural circuits in the esophagus. This function is composed of three distinct phases: preparatory/oral, pharyngeal and esophageal. In this context, the present study has as its main objective to examine the physiology of atypical swallowing, based on a comprehensive bibliographic review, addressing its main characteristics, causes and consequences within the period from 2018 to 2023. Atypical swallowing is associated with inadequate position of the tongue and other muscles involved in the process. During the mixed dentition phase, changes occur in the stomatognathic system, marking the transition from the infant swallowing pattern to the adult pattern. However, in certain situations, infant swallowing persists after replacement of the deciduous teeth, resulting in atypical swallowing. This may be related to prolonged bottle use, mouth breathing, and anatomical and central nervous system changes. Given this, it is essential that dentists are vigilant to identify early and accurately diagnose the different types of swallowing in order to provide effective oral rehabilitation and prevent recurrences. Effective treatment of atypical swallowing requires close collaboration between dentists and speech therapy professionals. In conclusion, this study achieved a deeper understanding of Atypical Swallowing, including its possible causes, impacts on affected individuals and therapeutic approaches aimed at a multidisciplinary approach.